Existence Results for Vector Variational-Like Inequalities: Rais Ahmad - Team, Support (Thai Journal of Mathematics, 2011)
The purpose of this work is to introduce and study a more general form of vector variational-like inequalities in Banach spaces. By using the definitions of h-n-quasimonotone of Stampacchia type and Minty type mappings, some existence results for vector variational-like inequalities are obtained. Some examples supporting the main results are also constructed.